The power of people: When people and culture are the key to organisations success - Da Costa, L. R.; Loureiro, S. M. C. (12th Annual Conference of the EuroMed Academy of Business: Business Management Theories and Practices in a Dynamic Competitive Environment, 2019)
INTRODUCTION This study intends to analyse the impact of people and culture’s management through engagement and employee experience towards the organisation’s success. In fact, after some research the data demonstrate that organisations understand the importance of retain and create happiness at work. The same organisations are starting to create a journey for their workforce: since the first day people have contact with the brand until the last day when they decide to leave or they go on the retirement and they take with them all the memories and experience, heritage with them. Organisations want and understand the need of having employees engaged, attract new talent, and retain team members, especially high performers and key people. This study reveals that when employees are more committed to be happier at work, they tend to take part of the ownership of their organisations. Today organisations are more focused on people and the value that they can add to every single product and/or service they design, create and deliver. Organisations want to feed a better and healthier culture founded on an inside-out mission and real values. All this investment on internal management is taking the consumer experience to a higher level. Happy and committed employees will create happier and more loyal clients.